A MULTICENTER STUDY OF BENIGN PROSTATIC HYPERPLASIA PATIENTS UNDERGOING TRANSURETHRAL RESECTION OF THE PROSTATE IN INDONESIA: A DESCRIPTIVE ANALYSIS - Daryanto, Besut; Penta Seputra, Kurnia; Satyagraha, Paksi; Nur Budaya, Taufiq; Kurniawan Dhani, Fauzan; Rasyidan Yulizar, Deddy; Hendry, Marta; Rhomdhon, Andrie; Ambeng, Yudi; Akhmad Adhi, Ryan (Indonesian Journal of Urology, 2025)
Objective: The study aims to provide a detailed understanding of the patient demographics and clinical features associated with TURP procedures in several tertiary hospital in Indonesia. Material & Methods: This study is a descriptive cross-sectional study conducted at four provinces in Indonesia. Patient data were collected from January 2021 to December 2023, including all patients diagnosed with BPH and who underwent TURP. The data were analyzed using the Statistical Package for Social Sciences (SPSS) version 28.0 (SPSS Inc., Chicago, Illinois, USA). Results: A total of 812 patients met the inclusion criteria for the study. The highest number of patients undergoing TURP (Transurethral Resection of Prostate) was at Saiful Anwar General Hospital, with 287 patients. The average prostate volume across all patients was 57.6±20.6 ml with an IPP (Intravesical Prostatic Protrusion) of 13.0±5.2 ml. Diabetes Mellitus was the most common comorbidity among the patients, affecting 271 patients (33.3%). Urinary retention was the most frequent reason for patients undergoing TURP, affecting 664 patients (81.7%), followed by bladder stones, which affected 58 patients (7.1%). Conclusion: Advanced age and a history of smoking are the primary clinical features observed in BPH patients undergoing TURP in Indonesia. Additionally, urinary retention has been identified as the main indication for TURP procedures in these patients. Keywords: TURP, BPH, IPP.